2002
DOI: 10.1039/b207438a
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel based optical carbon dioxide sensor employing dual luminophore referencing for application in food packaging technology

Abstract: An optical sensor for the measurement of carbon dioxide in Modified Atmosphere Packaging (MAP) applications has been developed. It is based on the fluorescent pH indicator 1-hydroxypyrene-3,6,8-trisulfonate (HPTS) immobilised in a hydrophobic organically modified silica (ormosil) matrix. Cetyltrimethylammonium hydroxide was used as an internal buffer system. Fluorescence is measured in the phase domain by means of the Dual Luminophore Referencing (DLR) sensing scheme which provides many of the advantages of li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(114 citation statements)
references
References 22 publications
3
107
1
1
Order By: Relevance
“…Optode technology has an advantage over conventional sensors in that it can also be used to assess oxygen distributions in 2 dimensions (e.g., Holst et al, 1997Holst et al, , 1998Glud et al, 1999Glud et al, Q1, 2001Glud et al, , 2005 and to detect other substances (e.g., Klimant et al, 2000;Huber et al, 2000Huber et al, , 2001aHuber et al, , 2001bHulth et al, 2002;von Bültzingslöwen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Optode technology has an advantage over conventional sensors in that it can also be used to assess oxygen distributions in 2 dimensions (e.g., Holst et al, 1997Holst et al, , 1998Glud et al, 1999Glud et al, Q1, 2001Glud et al, , 2005 and to detect other substances (e.g., Klimant et al, 2000;Huber et al, 2000Huber et al, , 2001aHuber et al, , 2001bHulth et al, 2002;von Bültzingslöwen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41]. One of the earliest studies reported in Table 2, used agarose as the encapsulation medium [32], but required a gas-permeable membrane to stop the film drying out and also to allow its use for making dissolved CO 2 measurements.…”
Section: Page 4 Of 25 Analystmentioning
confidence: 99%
“…These films usually suffer from poor stability unless used and stored either in water or under high humidity conditions [35,37].…”
Section: Page 4 Of 25 Analystmentioning
confidence: 99%
“…(9). Table 3 provides details of many of the dry luminescent optical films for carbon dioxide that have been reported in the literature [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] and, as with the wet indicators, reviewed earlier, see table 1, most are intensity-rather than lifetime-, based sensors. Almost all these sensors utilise the ion-pair technology developed by Mills et al 44,45 .…”
Section: Dry Optical Sensors For Carbon Dioxidementioning
confidence: 99%
“…A brief inspection of the many examples of dry luminescent indicator systems for carbon dioxide reveals that most of those reported to date are intensity-based and, amongst the few other, and admittedly more recent, examples, the FRET method of detection dominates. One other sensing method that doesn't fall into any of the categories considered so far, is the measurement of carbon dioxide levels using phasemodulated fluorimetry coupled with a Dual Lumophore Referencing (DLR) proposed by MacCraith et al 69 . In DLR, two different luminescence signals are generated in the sensing membrane by the modulated excitating light source; in this case a bright blue 470 nm LED.…”
Section: Dry Optical Sensors For Carbon Dioxidementioning
confidence: 99%